Ammonia-assisted dehydrofluorination between PVDF and Nafion for highly selective and low-cost proton exchange membranes: a possible way to further strengthen the commercialization of Nafion1. Issue 24 (28th June 2015) - Feng, Kai; Tang, Beibei; Wu, Peiyi
<x xml:space="preserve">Abstract</x> Low-cost PEM with high performance is prepared via dehydrofluorination reactions between PVDF and Nafion with the aid of ammonia.